Perspectives of teachers and parents towards a preschool intervention in Borneo: ToyBox Malaysia - Lee, J.A.; Cheah, Whye Lian; Anchang, G. N. J.; Hung, E.S; Poh, B.K.; Gibson, E. L. (Karger Publishers, 2019)
Although there are many studies on childhood obesity prevention including intervention studies on healthy energy balance-related behaviours in developed nations, such studies are scarce in Borneo. The aim of the present study was to elicit teachers’ and parents’ perspectives on a childhood intervention study: ToyBox Study Malaysia is aimed at improving healthy energy balance-related behaviours among preschoolers, focusing on healthy snacking, drinking water, reducing sedentary behavior, and increasing physical activity.